The Relationship Between Cholesterol And Aging In Patients With Type 2 Diabetes (Journal of Namibian Studies : History Politics Culture, 2023)
Although lipid-lowering medications (LLDs) are protective against cerebrovascular disease (CVD) and coronary artery disease (CAD), a paradoxical correlation between cholesterol and a number of illnesses, including atrial fibrillation, diabetes, and dementia, has been found. In older adults with type 2 diabetes mellitus (T2DM), we sought to examine the relationship between LLDs and cholesterol levels. Three Taiwanese centers recruited consecutive patients aged ≥50 years for this cross-sectional study. Age, triglyceride level, sex, comorbidities, and medication were taken into account when calculating odds ratios (ORs) for various levels of total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C) in comparison to the highest level using a multiple logistic regression model. Of the 3688 participants, 676 did not have type 2 diabetes and 572 did. Regardless of LLD use, the non-T2DM group outperformed the T2DM group in terms of daily functioning, medical conditions, and cognition after controlling for age and sex. As TC levels declined, ORs increased significantly in comparison to the maximum TC level (≥240 mg/dL). LDL-C levels showed a similar pattern of T2DM prevalence. T2DM in older adults was associated with poor cognitive and everyday functioning. Regardless of LLD use, a higher prevalence of T2DM in older adults was linked to significantly lower TC and LDL levels. Cognitive and everyday functioning impairment was linked to type 2 diabetes. When the "lower is better" approach is used for the secondary prevention of type 2 diabetes, a higher prevalence of the disease in older adults with low cholesterol levels raises concerns about how cognition and everyday functioning may be compromised.